The Influence of Profitability and Leverage on Tax Avoidance in Food and Beverage Companies Registered on BEI in 2019 - 2023 (Tri Wulan III) - Apriani, Rosini; Mulyani, Sri; Setiawati, Emy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The aim of this research is to determine the effect of profitability and leverage on tax avoidance carried out in food and beverage companies listed on the Indonesia Stock Exchange for the period 2019 - 2023 (Tri Wulan III). This research uses a quantitative method, namely by conducting verification research with an explanatory survey method, a method that aims to test hypotheses. The samples used in this research were 10 with a total of 50 data samples studied. The techniques used in this research are descriptive statistics, classical assumption tests, multiple linear regression hypothesis tests and coefficient of determination tests. The results of this research show that partially there is no significant influence of profitability and leverage on tax avoidance. Simultaneously, profitability and leverage do not have a significant effect on tax avoidance in food and beverage companies listed on the Indonesia Stock Exchange.